The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/0003134820982573
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Enhanced Recovery Program on Elective Right Hemicolectomies for Crohn’s Disease vs. Colon Cancer: A Retrospective Cohort Analysis

Abstract: Background Enhanced recovery after surgery (ERAS) protocols are widely employed in colorectal surgery, successful in reducing postoperative morbidities and hospital length of stay (LOS). However, ERAS effects on the inflammatory bowel disease population remain unclear. This study examines the postoperative course of both Crohn’s disease (CD) and colon cancer (CC) patients after elective right hemicolectomies and compares the effectiveness of ERAS protocol. Methods A retrospective analysis was performed on pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
1
1
Order By: Relevance
“…In our study, overall incidence of PPOI was 42.7%, which was higher than in previous studies that reported an incidence of 10 to 30% [5][6][7]23]. This difference could be explained since our cohort includes exclusively CD patients, who have a known higher risk for PPOI [24,25]. Furthermore, although the definitions of POI and PPOI were extensively discussed in various studies before, their inconsistent use in the literature contributes to incomparable results about the incidence and the risk factors of PPOI.…”
Section: Discussioncontrasting
confidence: 74%
“…In our study, overall incidence of PPOI was 42.7%, which was higher than in previous studies that reported an incidence of 10 to 30% [5][6][7]23]. This difference could be explained since our cohort includes exclusively CD patients, who have a known higher risk for PPOI [24,25]. Furthermore, although the definitions of POI and PPOI were extensively discussed in various studies before, their inconsistent use in the literature contributes to incomparable results about the incidence and the risk factors of PPOI.…”
Section: Discussioncontrasting
confidence: 74%
“…While other studies have shown similar reductions in LOS after the introduction of ERAS in surgery for IBD, none have reported an IBD-specific ERAS pathway [ 15 19 ]. Preoperative counseling with an IBD surgeon in the outpatient clinic, intravenous iron treatment for patients with iron-deficiency anemia, and preoperative risk stratification for anastomotic leakage were some of the items added to our department’s ERAS protocol utilized for patients undergoing surgery for colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%